2023
DOI: 10.1039/d3tc02074f
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-plasma induced one-step synthesis of Ni(PO3)2 nanosphere-loaded bio-waste derived N, P co-doped carbon for an asymmetric supercapacitor with prolonged life

Nisha Gupta,
Pallab Bhattacharya

Abstract: Ni(PO3)2 nanospheres and bio-waste derived N, P co-doped carbon composites as asymmetric supercapacitor with long cycle life to run an oximeter and 28 LEDs demonstrating a strong practical application prospect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 88 publications
0
11
0
Order By: Relevance
“…Therefore, the optical microscopic images and FTIR study confirm that ball milling not only reduced the agglomeration and particle sizes but also created more oxygenated dipoles like −C−O, −C�O, and −OH to influence the microwave absorption of MAP 2 through the dipolar polarization mechanism. 30 Smaller particle sizes and low agglomerations may also help to boost the surface area of MAP 2, which can eventually increase its contact area with microwave-irradiated radiation 31 for better microwave absorption.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Therefore, the optical microscopic images and FTIR study confirm that ball milling not only reduced the agglomeration and particle sizes but also created more oxygenated dipoles like −C−O, −C�O, and −OH to influence the microwave absorption of MAP 2 through the dipolar polarization mechanism. 30 Smaller particle sizes and low agglomerations may also help to boost the surface area of MAP 2, which can eventually increase its contact area with microwave-irradiated radiation 31 for better microwave absorption.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…However, the process of ionizing N 2 gas to generate N 2 plasma through microwave irradiation has been previously explored in one of our recent publications. 30 Interestingly, it is seen that the kinetics of plasma formation vary significantly during the preparation of NGC and HP-NGC. In the process videos (Movies S1 and S2), it was observed that plasma formation started immediately (within ∼2−5 s) during the preparation of HP-NGC, whereas for NGC, the plasma state appeared almost 5 times slower (after ∼25 s).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations